Caracterização da tolerância e das respostas fisiológicas a diferentes protocolos de exercício intervalado de alta intensidade em pacientes com doença pulmonar obstrutiva crônica - Bravo, Daniela Manzoli [UNIFESP] (2016)
to the limit of tolerance (Tlim) or up to 30 min: a CWE test at 75-80% of the previously-determined peak work rate (WR); and four HIIE tests with 100% peak WR during high-intensity bouts, in which both duty cycle duration (30s/60s vs. 60s/120s) and relief interval intensity (free wheel (FW) or 40% peak WR) were applied: i) EI 1 - 30s/60s interspersed with FW; ii) EI 2 - 30s/60s interspersed with 40% peak WR; iii) EI 3 - 60s s interspersed with FW and iv)E - s s interspersed with pea W . he following variables were evaluated dyspnoea and leg fatigue symptoms ventilation E and ventilatory reserve E maximal voluntary ventilation (MVV)); operating lung volumes (end inspiratory lung volume (EILV)/total lung capacity (TLC) and inspiratory residual volume (IRV)); respiratory gas exchange (oxygen consumption ( O2) and carbon dioxide production ( O2)); arterialized blood lactate; heart rate (HR) and non-invasive cardiac output. Results: CWE presented with lower Tlim and total work performed than all HIIE protocols and higher metabolic ( O2, O2 and blood lactate), cardiovascular (HR) and ventilatory (higher E, lower E/ CO2) responses, lower SpO2 and a steeper increase in symptoms than EI 1 and EI 3 protocols. Furthermore, CWE lead to higher ventilatory limitation (higher E/MVV and EILV/TLC and lower IRV) than EI 1 protocol. EI 1 presented with lower metabolic O2 O2 and blood lactate), cardiovascular (HR) and ventilatory responses, with lower ventilatory constraints (lower EILV/TLC and higher IRV) than EI 2 and EI 4 protocols. EI 1 and EI 3 were tolerated up to 30 minutes in 14 (87%) and 13 (81%) patients, respectively; with higher time spent at high-intensity bouts than EI 2 protocol. Nine (56%) patients did not tolerate EI 2 and EI 4 protocols, with higher ventilatory constraints (higher EILV/TLC and lower IRV) at the end of exercise and a steeper increase in blood lactate, CO2, E and symptoms during exercise than patients who tolerate these protocols. Conclusions: HIIE protocols were more tolerated than high-intensity CWE in our COPD patients. Duty cycle duration did not affect tolerance to HIIE. However, loaded exercise in-between the high-intensity bouts increased metabolic, cardiovascular and ventilatory responses to exercise and reduced tolerance to HIIE in a substantial percentage of patients who presented with higher ventilatory constraints.